KONSEP KEPEMIMPINAN DALAM PERSPEKTIF AL-QUR’AN - Suhartawan, Budi (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
In a country and society, a leader is needed who is able to guide and guide the community. Leadership is every person's effort to influence a person's behavior or group behavior. Attempts to influence this behavior to achieve individual or group goals. The purpose of this study is to analyze how the concept of leadership is in the perspective of the Qur'an, how to understand what leadership means in the Qur'an, and what are the instructions of the Qur'an regarding leadership. This research is included in the category of library research, because it analyzes documents and sources of information related to what is being studied. While the interpretation method used is the Maudu'i interpretation method. From the results of this research, it can be explained that the concept of leadership in the perspective of the Qur'an, is seen as the ability of a leader to set an example, guide and convince those he leads consciously and voluntarily to carry out activities to achieve common goals from what is targeted in his leadership. The characteristics of leadership in the perspective of the Qur'an are having a spirit of trust, prioritizing deliberation, responsibility, and being able to be fair to those they lead. In addition, the essence of Qur'anic leadership is not only for worldly interests, but rather for accountability to Allah swt.